Orbital inflammatory complications of Crohn’s disease: a rare case series - Monaghan, Tanya M.; Albanese, Giorgio; Kaye, Philip; Thomas, James D.; Abercrombie, Lorraine; Moran, Gordon W. (SAGE, 2018)
Orbital inflammatory disease is a rare ophthalmic manifestation of Crohn’s disease. Inflammation is characteristically non-specific, involving one or multiple structures of the orbit. Mechanisms of disease and optimal methods of treatment are poorly understood. The aim of this report is to present three cases of orbital involvement in Crohn’s disease. A retrospective case note review of patients with orbital inflammatory disease and Crohn’s disease was performed at our academic centre to determine the clinical, imaging and histopathological features of this condition and its relationship to intestinal Crohn’s disease. Three patients were identified with orbital inflammatory manifestations complicating Crohn’s disease. All patients described were female with active intestinal disease and had a history of treatment with immunosuppressive therapies. Similarities were observed in clinical presentations with variance noted in radiological and histopathological findings. In all cases, symptoms improved with oral corticosteroids or non-steroidal drugs in combination with anti-tumour necrosis factor (anti-TNF) agents. Inflammatory bowel disease-related orbital complications are rare but potentially vision-threatening. It is important to consider mimics of orbital inflammatory disease such as systemic inflammatory disease, malignancy, congenital malformations, infection and trauma when formulating a comprehensive differential diagnosis. Therapeutic intervention is directed towards preservation of vision and orbital function and reducing the acute inflammatory process. Corticosteroids are typically the initial treatment of choice for moderate-to-severe disease, although several classes of immunomodulatory agents have been variably useful in treating this condition. Heightened awareness and close cooperation between gastroenterologists and ophthalmologists is mandatory.